Penguasaan Technological Content Knowledge (TPACK Mahasiswa Calon Pengajar Dalam Menunjang Pembelajaran Digital) - Rosmaladewi, Okke; Yulyul Yuliana Hastuti, Raden; Rahayu, Puji (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This study aims to discuss the importance of mastering TPACK for prospective teaching students in their readiness to become a teacher with digital learning. Mastery of TPACK must be owned by a prospective teacher in welcoming learning in the industrial era 4.0. Therefore, prospective teaching students need TPACK in making learning media innovations. Because learning media is one of the supporting factors in learning effectiveness.The hope is that by using TPACK, prospective teaching students can apply TPACK skills in real classes when they have graduated from educational science courses. This study uses content analysis or literature studies on a number of articles that have been published in educational journals from 2017 to 2022 regarding TPACK mastery of prospective teachers in digital learning. The purpose of this literature review is to see an overview of the prospective teacher's TPACK mastery in supporting digital learning. The results of a literature review of research articles show that prospective teachers must be able to convey material content by integrating technology into learning. technology in learning.